Evaluation of Carotid Artery Stenosis with Multisection CT and MR Imaging: Influence of Imaging Modality and Postprocessing - Lell, M.; Fellner, C.; Baum, U.; Hothorn, T.; Steiner, R.; Lang, W.; Bautz, W.; Fellner, F.A. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We prospectively evaluated the influence of different imaging techniques (time-of-flight MR angiography [TOF-MRA], contrast-enhanced MR angiography [CE-MRA], multisection CT angiography [CTA]) and postprocessing methods (maximum intensity projection [MIP], multiplanar reformation [MPR]) on carotid artery stenosis grading.MATERIALS AND METHODS: Fifty patients (34 men, 16 women) with symptomatic stenosis of the internal carotid artery were examined with a 16-section spiral CT and a 1.5T MR unit. Two MRA techniques were applied: 3D-TOF and CE-MRA. MPR was used for postprocessing with all modalities; MIP was used only with MRA. Four readers measured and calculated the percentage diameter stenosis independently according to NASCET criteria. The Wilcoxon test was used to measure interobserver variability, and the Friedman test was used to test the null-hypothesis of equality of the modalities.RESULTS: The hypothesis for global equality was rejected (P < .001). TOF-MRA and CTA assessed with MPR showed the highest concordance (difference, 0.6%; confidence interval [CI], −3.0, 4.3%), and CE-MRA with MIP and CTA showed the lowest concordance in stenosis grading (difference, 7.0%; CI, 3.4, 10.6%). MPR resulted in lower degrees of stenosis than MIP for both MRA sequences, although not statistically significant (CE, −3.0%; CI, −6.6, 0.6%; TOF, −2.2%; CI, −5.8, 1.4%). When only studies with good or excellent image quality were considered, the differences decreased, but the trends remained.CONCLUSION: Stenosis grading is dependent on the examination method and postprocessing technique. CTA and TOF-MRA evaluated with MPR revealed highest concordance.